The ethnobotanical study on screwpine (Pandanus odoratissimus L.f.): usage and importance in supporting the domestic economy of the local people in Ujung Kulon, Banten - MULYATI RAHAYU; SITI SUNARTI; ARY PRIHARDHYANTO KEIM (Society for Indonesian Biodiversity, 2008)
The local people of Ujung Kulon use the leaves of screwpine (Pandanus odoratissimus L.f.) for their daily purposes,especially making mats. The people recognise two entities of pandanus/screwpine as two different taxa, the â€œpandan samakâ€ and â€œpandan lautâ€. Both are identified here as belonging to P. odoratissimus. The two taxa are regarded closely related, in which the â€œpandan lautâ€ is believed to be the wild type of the domesticated â€œpandan samakâ€. Its cultivated in Ciundil. Although P. furcatus Roxburgh and P. dubius Sprengel are also recognised, neither is used as source of mats.Key words: ethnobotany, pandan, Pandanus odoratissimus L.f., Ujung Kulon